PENGARUH INVESTASI, TENAGA KERJA DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Mutia Sari; Mohd. Nur Syechalad; Sabri Abd. Majid (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2016)
This study aims to determine investment, labor and government spending to economic growth in Indonesia. Estimation results indicate that simultaneous variable investment, labor and government spending have a significant effect on the growth of ekonomi.di Indonesia. Economic growth can be explained by the variable investment, labor and government spending ebesar 74.1 percent and the remaining 25.9 percent can be explained by other variables not included in this study. The estimation results of labor variables significant and positive impact on economic growth in Indonesia. Hasil estimates for investment variables significant and positive impact on economic growth in Indonesia. Results estimates for government expenditure variable significant and positive impact on economic growth in Indonesia.